Высокотемпературное испарение капель воды в газовой среде; Журнал технической физики; Т. 87, вып. 12 - Войтков И. С. Иван Сергеевич; Волков Р. С. Роман Сергеевич; Кузнецов Г. В. Гений Владимирович; Стрижак П. А. Павел Александрович (2017, 2017)
Заглавие с экрана